Social Media Addiction among Women who Underwent Cosmetic Breast Augmentation Surgery - Öztürk, Güncel; Beyazyüz, Elmas; Albayrak, Yakup (Addicta: The Turkish Journal on Addictions, 2021)
There is a growing belief that people who undergo aesthetic procedures such as rhinoplasty and breast augmentation are more prone to social media addiction. In the present research, we aimed to compare the level of social media addiction between women who underwent breast augmentation surgery and age- and education-matched controls. Based on the inclusion and exclusion criteria, 52 women who underwent breast augmentation surgery and 50 age- and education-matched healthy women participated in the study. These groups were compared with respect to social media addiction, self-esteem, and body satisfaction. The case group had significantly higher scores on the social media addiction scales (SMAS) than the control group (p = .001). A total of 40 (76.93%) patients in the case group scored above the cutoff point of 74 on the SMAS, compared to 21 (42%) individuals in the control group. The prevalence of addiction was higher in the case group (p = .001). The present study is the first to demonstrate a higher rate of social media addiction in the special population of breast augmentation surgery patients. As this surgery is elective rather than vital, surgeons should screen the psychological status of women who undergo this surgical procedure.